Pengaruh Intervensi Edukasi Perilaku Hidup Bersih dan Sehat (PHBS) Terhadap Peningkatan Pengetahuan dan Perilaku Siswa Sekolah Dasar di Aceh Besar - Ricky Dear Fitria; Ambianurdin Ambianurdin; Zoel Helmi; Bukhari Bukhari; Mardhiah Mardhiah (Public Health Journal, 2026)
This study employed a quasi-experimental one-group pre–post test design to assess the effectiveness of an educational intervention on Clean and Healthy Living Behavior (PHBS) in improving students’ knowledge and behavior. The program was conducted over four months (September–December 2024) involving 60 students from grades IV,V and VI. The intervention consisted of socialization, demonstrations, behavioral evaluations, and integration of supporting activities in literacy, numeracy, technology, character, spirituality, and arts. Results showed a significant improvement in students’ knowledge and PHBS practices, with the mean knowledge score increasing from 8.21 to 12.67 (p < 0.001), representing a 54.3% relative improvement. Positive behavioral changes were observed, such as proper handwashing, maintaining nail and oral hygiene, and classroom cleanliness. The integration of digital learning media such as Wordwall and Canva, along with educational games, enhanced student motivation and engagement. This participatory approach also strengthened teacher involvement and fostered a cleaner, more disciplined, and collaborative school culture. In conclusion, the PHBS educational intervention was proven effective in improving students’ health knowledge and behavior and can be replicated in other elementary schools as a collaborative, health-based learning model.